Lean Thinking in civil construction with the help of methods from psychology - Sousa, Anna Carolina Rodrigues de; Ramos, Amanda Lemes Caldeira; Sakai, Erika (Seven Editora, 2024)
Since civil construction is a field that needs human labor on a daily basis, Lean Thinking seeks a better production, with fewer errors and waste of value. For the implementation of the system, it is necessary to apply other methods, coming from psychology and capable of studying the different types of personalities, which are the Enneagram and NEO-FFI, being linked to each other. In order to verify the variation in the production of the activities in which the tools are applied, a study was carried out in the form of a questionnaire about a management system capable of increasing production and improving quality in civil construction, through the identification of the profiles of people with the greatest deficit in the identified services. The study was carried out in two works in the city of Goiânia, and it was possible to carry out a training based on the treatment mode of each profile and thus analyze the results obtained about it, the activities that were part of the study, presented a better production, progressing by 38.78% and 19.57% in works 1 and 2 respectively, thus generating savings and proving efficiency of the methods adopted. DOI:https://doi.org/10.56238/sevened2023.006-153